The Effectiveness Of Using Column Formwork In A Multi-Story Building Construction Project - Vansya, Muhammad Lawdy Dhiyaa; Arifi, Eva; Wijaya, Ming Narto (Rekayasa Sipil, 2024)
Building the structural components is crucial for constructing a multi-story building. In the process of creating these components, which is commonly done through casting, a tool called formwork is required. Formwork is a tool used to mold the necessary concrete structures, ensuring that their shape and dimensions align with the concrete material's planning. Formwork tasks for concrete work significantly impact costs. Different formwork options, including traditional, semi-system, and full-system forms, are available. This research aims to assess cost-effectiveness through value engineering, specifically focusing on column formwork, by comparing their utilization in a multi-story construction project. The study begins by collecting primary data, namely working drawings, so that the volume of conventional formwork can be calculated. Then, budget planning calculations are made to analyze the cost comparison of each formwork alternative. The selection of the appropriate formwork affects the speed of execution and the costs incurredIn this construction project for the building, the conventional column formwork results in expenses amounting to IDR 587,749,263.04 and requires 28 days for completion, while semi-system column formwork achieves a 37% cost saving with the same duration of 28 days, and full-system column formwork becomes 64% more cost-effective with a construction period of 10 days.